Non-stationary components fixing Jacobi iteration - Jun Srisutapan (2018)
This paper presents an effective extension to the classical Jacobi iteration. The non-stationary components fixing Jacobi iteration was designed to save the computational cost per iteration. This done by skip evaluating the solution components that probably need no computation in a certain iteration. The experiment using PDE data set confirm our method. Moreover, the quality of the obtained solutions are acceptable.